2017
DOI: 10.1098/rspb.2017.1300
|View full text |Cite
|
Sign up to set email alerts
|

Temperate marine protected area provides recruitment subsidies to local fisheries

Abstract: The utility of marine protected areas (MPAs) as a means of protecting exploited species and conserving biodiversity within MPA boundaries is supported by strong empirical evidence. However, the potential contribution of MPAs to fished populations beyond their boundaries is still highly controversial; empirical measures are scarce and modelling studies have produced a range of predictions, including both positive and negative effects. Using a combination of genetic parentage and relatedness analysis, we measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 48 publications
2
51
0
Order By: Relevance
“…Parent–offspring pairs in this study demonstrate direct connectivity between no‐take reserves from the network of MPAs surrounding the Monterey Peninsula, as well as between these conservation areas and adjacent areas where recreational fishing is allowed. This second phenomenon confirms the “spillover effect” or “recruitment cross‐subsidy” (Le Port et al, ), whereby reproduction within reserves replenishes fished populations, as larvae born inside protected areas disperse. Connectivity of habitat patches at a local scale reinforces the benefit of marine reserve “networks” that conserve characteristic environments, particularly productive, nearshore, temperate rocky reefs.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Parent–offspring pairs in this study demonstrate direct connectivity between no‐take reserves from the network of MPAs surrounding the Monterey Peninsula, as well as between these conservation areas and adjacent areas where recreational fishing is allowed. This second phenomenon confirms the “spillover effect” or “recruitment cross‐subsidy” (Le Port et al, ), whereby reproduction within reserves replenishes fished populations, as larvae born inside protected areas disperse. Connectivity of habitat patches at a local scale reinforces the benefit of marine reserve “networks” that conserve characteristic environments, particularly productive, nearshore, temperate rocky reefs.…”
Section: Discussionsupporting
confidence: 62%
“…Tracking larval dispersal in the ocean is considered one of the great logistical challenges in marine ecology (Pineda, Hare, & Sponaugle, ). Studies that have successfully addressed this challenge have produced intriguing results regarding the prevalence of self‐recruitment (Berumen et al, ; Jones, Planes, & Thorrold, ), connectivity among reefs (Almany et al, ; Christie et al, ) and the effectiveness of marine reserves (Harrison et al, ; Le Port et al, ; Planes, Jones, & Thorrold, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that the no-take areas are providing refuge for larger C. auratus, a species susceptible to reduced population resilience through age-class truncation (Stewart, 2011), these no-take areas could potentially contribute to rebuilding of local populations as the larger fish are more likely to have higher fecundity and quality of eggs (Berkeley et al, 2004;Stewart et al, 2009). In a recent study in New Zealand, it was demonstrated through genetic parentage and relatedness analysis that adult C. auratus within a no-take reserve contributed newly settled juveniles to surrounding areas (Le Port et al, 2017). Whilst the increased abundance and size of C. auratus within the no-take areas could be contributing to other areas of the marine park by way of larval dispersal and newly settled juveniles, the fishery benefit of this is yet to be quantified and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%